Multiple systemic metastases of posterior fossa - primitive neuroectodermal tumor (PF-PNET) in adult: case report - João Paulo Mattos; Leonardo Bonilha; Daniele Ferreira; Wilson Borges; Yvens Barbosa Fernandes; Guilherme Borges (Arquivos de Neuro-Psiquiatria)
We present the case of a 30-year female patient with multiple systemic metastases of posterior fossa primitive neuroectodermal tumor (PF- PNET) and present a review concerning the usual presentation, sign and symptoms, radiological aspects, pathways of spread, genetic patterns and treatment of PF-PNET. The biological behavior of PF - PNET is analyzed taking into consideration the presence of systemic metastases.